2019
DOI: 10.1007/s11357-019-00069-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel individualized power training protocol preserves physical function in adult and older mice

Abstract: Sarcopenia, the age-related loss of muscle mass and strength, contributes to frailty, functional decline, and reduced quality of life in older adults. Exercise is a recognized therapy for sarcopenia and muscle dysfunction, though not a cure. Muscle power declines at an increased rate compared to force, and force output declines earlier than mass. Thus, there is a need for research of exercise focusing on improving power output and functionality in older adults. Our primary purpose was proof-of-concept that a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
(80 reference statements)
2
14
0
Order By: Relevance
“…To examine whether the same relationship is observed in muscles that have been subjected to WP, we first measured various structural properties of the plantaris muscle. We initially focused on the plantaris because this has been one of the most widely studied muscles in other mouse models of PRE, and as shown in Figure 3K, WP led to a modest but significant increase in its mass [17,20,34]. Our structural analyses also revealed that 13 weeks of WP did not alter the resting length of the plantaris, but it did lead to a 21% increase in the mid-belly CSA (Fig.…”
Section: Wp Induces Hypertrophy and Myonuclear Accretion In The Plantaris Musclementioning
confidence: 83%
“…To examine whether the same relationship is observed in muscles that have been subjected to WP, we first measured various structural properties of the plantaris muscle. We initially focused on the plantaris because this has been one of the most widely studied muscles in other mouse models of PRE, and as shown in Figure 3K, WP led to a modest but significant increase in its mass [17,20,34]. Our structural analyses also revealed that 13 weeks of WP did not alter the resting length of the plantaris, but it did lead to a 21% increase in the mid-belly CSA (Fig.…”
Section: Wp Induces Hypertrophy and Myonuclear Accretion In The Plantaris Musclementioning
confidence: 83%
“…To examine whether the same relationship is observed in muscles that have been subjected to WP, we first measured various structural properties of the plantaris muscle. We initially focused on the plantaris because this has been one of the most widely studied muscles in other mouse models of PRE, and, as shown in Figure 3 K, WP led to a modest but significant increase in its mass [ 17 , 20 , 34 ]. Our structural analyses also revealed that 13 weeks of WP did not alter the resting length of the plantaris, but it did lead to a 21% increase in the mid-belly CSA ( Figure 4 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…During the last 50 years, a variety of different animal models have been used to develop a better understanding of how PRE induces an increase in muscle mass. The majority of these models have involved the use of rodents, with earlier models largely relying on rats and more recent models relying on mice [ 15 , 16 , 17 , 18 , 19 ]. Mouse models are now viewed as being particularly advantageous because they are amenable to the wide array of genetic inventions that are often paramount to mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, myoblasts are shown to have a long-term epigenetic memory of previous exposure to stress in vitro 75 , so satellite cells could theoretically contribute to muscle memory in myofibers via recently identified fusion-independent mechanisms in vivo. 76 Future studies may employ newly developed voluntary 77 or involuntary resistance training paradigms (exercise dosage can be controlled for in the latter) 78,79 for mice that can complement PoWeR (recently reviewed here 31 ) and will aim to address how myonuclei are removed during detraining, the role of myonuclear translocation during exercise adaptation, whether epigenetic changes could explain myonuclear shape transformations with training and detraining, which exercise-induced epigenetic alterations to myonuclei are permanent, and how miR-1 could facilitate retraining adaptations.…”
Section: Discussionmentioning
confidence: 99%